Laser ignition and controlled explosion of nanoenergetic materials: The role of multi-walled carbon nanotubes. (July 2017) - Kim, Ji Hoon; Cho, Myung Hoon; Kim, Kyung Ju; Kim, Soo Hyung
Abstract: Laser irradiation permits the remote ignition of nanoenergetic materials (nEMs). To reliably ignite nEMs with lower-power laser irradiation, light-sensitive materials could be added to the nEMs matrix. In this study, we investigated the effects of multi-walled carbon nanotubes (MWCNTs) on the combustion and explosion characteristics of laser irradiation-ignited nEMs. The threshold power and delay time of ignition gradually decreased with increases in the MWCNT contents of Al nanoparticle (NP)/CuO NP-based nEMs. The threshold power and delay time of MWCNT (10 wt%)/Al NP/CuO NP ignition were reduced to ∼40% and ∼50%, respectively, of those of MWCNT (0 wt%)/Al NP/CuO NP. This suggests that the MWCNTs act as effective optical igniters by absorbing irradiated laser beams and subsequently generating heat by the photo-thermal effect, promoting nEMs ignition. The optimal addition of ≤2 wt% MWCNTs in the nEMs matrix enhanced the pressurization rate, flame propagation speed, and pressure wave speed of nEMs because the MWCNTs rapidly transferred heat energy from nEMs combustion. However, adding excess MWCNTs suppressed the combustion and explosion characteristics of the Al NP/CuO NP-based nEMs matrix by heat dissipation and thermochemical interventions. This suggests that MWCNTs can potentially control the combustion and explosion characteristics of Al NP/CuO NP-based nEMs. Graphical abstract: